2019
DOI: 10.1073/pnas.1904975116
|View full text |Cite
|
Sign up to set email alerts
|

Neural substrates of sexual arousal are not sex dependent

Abstract: Sexual arousal is a dynamical, highly coordinated neurophysiological process that is often induced by visual stimuli. Numerous studies have proposed that the cognitive processing stage of responding to sexual stimuli is the first stage, in which sex differences occur, and the divergence between men and women has been attributed to differences in the concerted activity of neural networks. The present comprehensive metaanalysis challenges this hypothesis and provides robust quantitative evidence that the neurona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 48 publications
(58 reference statements)
4
28
0
Order By: Relevance
“…Thereby, the spatiotemporal scale of consideration and context are critical. While functional systems level studies question the presence of sexual dimorphisms within reward circuitry with respect to sexual arousal (Mitricheva, et al, ; Stark, et al, ), cellular and molecular sex differences associated with addiction may still be present within the same network (Sanchis‐Segura and Becker, ; Huber, et al, ; Becker and Chartoff, ). In addition to context and scales of consideration, the proper sample size, choice of statistical methods and data convergence may further influence the outcome of investigations and thus, conclusions made on sex differences.…”
Section: Discussionmentioning
confidence: 99%
“…Thereby, the spatiotemporal scale of consideration and context are critical. While functional systems level studies question the presence of sexual dimorphisms within reward circuitry with respect to sexual arousal (Mitricheva, et al, ; Stark, et al, ), cellular and molecular sex differences associated with addiction may still be present within the same network (Sanchis‐Segura and Becker, ; Huber, et al, ; Becker and Chartoff, ). In addition to context and scales of consideration, the proper sample size, choice of statistical methods and data convergence may further influence the outcome of investigations and thus, conclusions made on sex differences.…”
Section: Discussionmentioning
confidence: 99%
“…biases) are more favorable for women whose partners use condoms. While some studies have reported male vs. female differences of neurobiological and behavioral responses to sexual stimuli (Rupp and Wallen, 2008;Hill et al, 2011), a recent meta-analysis found that females and males generally activate the same brain regions in response to sexual cues (Mitricheva et al, 2019). In addition, while a recent study found that differential patterns in the subcortical response to non-sexual cues between males vs. females were predictive of sexual risk behaviors (Victor et al, 2015), it is unclear whether there would be differences in the mesolimbic response to sexual cues between males vs. females with varying degrees of STIs/HIV sexual risk behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…Significant nodes within the cue-reactive mask (e.g., dorsal striatum, insula) that differed between the Protected and Unprotected groups have been shown to be involved in the processing of visual sexual stimuli (Mitricheva et al, 2019). The caudate and putamen process both positive and negative stimuli (Lammel et al, 2014), driving reward-seeking behaviors and motivational states (Wise, 2004), such as pleasurable eating (e.g., Small et al, 2003), drug craving (e.g., Breiter et al, 1997;Wong et al, 2006;Volkow et al, 2006), sexual-related activities (see review, Gola and Draps, 2018), and the pursuit and loss of monetary value (e.g., Knutson et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, on the basis of a review of studies of sex differences in human brain structure, Eliot concluded that when brain size is controlled for, sex category accounts for less than 2% of the variability in brain structure ( 19 ). Recent studies, which assessed the contribution of several factors to variability in brain function (measured using functional MRI), reported that sex category explained only a small fraction of this variability ( 20, 21 ). Finally, an assessment of the relations between the number of sex differences in functional MRI studies and sample size did not reveal the positive correlation expected if brain function of women and men belonged to two populations ( 22 ).…”
Section: Discussionmentioning
confidence: 99%